1996
DOI: 10.1002/ana.410400412
|View full text |Cite
|
Sign up to set email alerts
|

Interferon beta induces interleukin‐10 expression: Relevance to multiple sclerosis

Abstract: Interferon-beta decreases the relapse rate, relapse severity, progression of neurological disability, and development of new brain lesions observed with brain magnetic resonance imaging in relapsing-remitting multiple sclerosis patients. The mechanism of action of this effect is presently unknown. This study was based on the hypothesis that immunoregulatory effects of interferon-beta may underlie its demonstrated clinical efficacy. The objective of the study was to determine the effect of interferon-beta-1a on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
110
0
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(122 citation statements)
references
References 53 publications
6
110
0
4
Order By: Relevance
“…IFNb is capable of promoting expression of a variety of cytokines and chemokines, including IL10, RANTES(CCL5), MCP-1(CCL2), MCP-3(CCL7), MCP-2(CCL8), MIG(CXCL9) and IP-10(CXCL10). [26][27][28] Because an elevated expression of cytokines and chemokines has been proposed to contribute to the unusual severity and mortality of H5N1 infection, 29,30 our results provide evidence in support of the hypothesis that the high pathogenicity of H5N1 virus may be associated with a reduced repression on IFN production conferred by the D92E mutation.…”
Section: Effects Of H5n1-ns1 Variants On Ifn Induction Wz LI Et Al 239supporting
confidence: 77%
“…IFNb is capable of promoting expression of a variety of cytokines and chemokines, including IL10, RANTES(CCL5), MCP-1(CCL2), MCP-3(CCL7), MCP-2(CCL8), MIG(CXCL9) and IP-10(CXCL10). [26][27][28] Because an elevated expression of cytokines and chemokines has been proposed to contribute to the unusual severity and mortality of H5N1 infection, 29,30 our results provide evidence in support of the hypothesis that the high pathogenicity of H5N1 virus may be associated with a reduced repression on IFN production conferred by the D92E mutation.…”
Section: Effects Of H5n1-ns1 Variants On Ifn Induction Wz LI Et Al 239supporting
confidence: 77%
“…Given the potential benefits of increased IL-10 and potential harm of IL-12, several groups have reported improvements in the ratio of IL-10 to IL-12 with IFN-β treatment (Correale et al, 1995,Rudick et al, 1996,Wang et al, 2000,Byrnes et al, 2002, Berghella et al, 2005, Ersoy et al, 2005. We confirmed these prior reports of overall improved ratios of serum IL-10/ IL-12p70 with IFN-β treatment and found that ratios of serum IL-10/IL-12p70 decreased in non-responders to therapy compared to pre-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-β has been shown to decrease clinical and MRI measures of disease activity in MS (Interferon Beta Study Group 1993, Paty et al, 1993,PRISMS 1998,Simon et al, 1999. IFN-β acts to increase IL-10 levels and reduce IL-12 levels in MS patients, thus improving the ratio of IL-10 to IL-12 (Correale et al, 1995,Rudick et al, 1996,Wang et al, 2000,Byrnes et al, 2002, Berghella et al, 2005, Ersoy et al, 2005. The mechanism of IL-12 suppression has been shown to depend on IL-10 induction (Wang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased IL-10 and increased IL-12 p40 mRNA are associated with disease activity [29]. IFN-b treatment influences cytokine levels with increasing Th2 cytokine production [30,31] and decreasing proinflammatory Th1 cytokine production [32].…”
Section: Discussionmentioning
confidence: 99%